Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Keywords: India; agrarian studies